The Markets of Society. A Research Design on Trans-Economic Exchange Rates - Steffen Roth (Dilemmata: Jahrbuch der ASFPG, 2009)
The first ambition of this paper is to present and argue for a concept of non-economic markets based on specific values (power, truth, justice, religion, etc.). The problem with these values is that they can neither be directly compared with money nor with each other: truth may be power, but how much? Would you prefer health or truth? What is the (non-)economical return of a bachelor degree? Nonetheless, every day we compare these incommensurable values. So there must be informal exchange rates. The analysis of these trans-economic exchange rates is as important as the analysis of the exchange rates between currency systems within the economic system. Based on the Luhmannian concept of functional differentiation, we are sketching a future research program based on the analysis of value related items of micro-databases (like the European Social Survey, for example). These items will be assigned to distinctive value categories. The unit of analysis then will be the intensity of dis- /affirmation to value related items: the more extreme dis-/affirmation to values of a certain value category is expressed, the higher is the relevance of the value category. By comparing these absolute values of the value categories we will calculate their relative value. It will be most interesting to focus and to compare the specific exchange rates of certain geographical segments or levels of population of European society: do the French think that politics is more relevant than the economic system? Do Estonians prefer science or education? What is the number one value category in Luxemburg? Which Sinus milieus like art more than health?
Keywords: A14; Z13; 330; Market; Function system; Functional differentiation; Luhmann